Evaluation of anti-bacterial IgG antibodies among rheumatoid arthritis and non rheumatoid arthritis patients with special reference to anti Proteus antibodies - HRV, Raj Kumar; Devaki, Ramahrishna; Kandi, Venkataramana (International Journal of Research in Medical Sciences, 2016)
Background: The objective of the study was to detect IgG antibodies against commonly isolated bacterial species among rheumatoid arthritis (RA) and non rheumatoid arthritis patients sera with special reference to anti Proteus antibodies. Methods: Fifty each of Rheumatoid factor positive, Rheumatoid factor negative, C reactive protein positive and C reactive protein negative sera were tested for IgG antibodies against ‘O’ antigens of Proteus mirabilis, Escherichia coli, Klebsiella pneumoniae, Salmonella typhi and Pseudomonas aeruginosa by indirect ELISA method using inactivated whole cells as the antigen. Results: Anti Proteus antibodies were detected in more number of (29/50) RA patients than non RA patients. The antibodies to other bacteria were detected in less number of sera. More number of C reactive protein positive sera was showing IgG antibodies to several bacterial pathogens than C reactive protein negative sera. Conclusions: Elevated levels of anti Proteus antibodies among RA patients clearly demonstrates the role of infectious agents in diseases like RA but it is not clear whether this role is a cause or effect. Further studies with large series at multiple centers may widen the treatment options for RA in future.